Upaya Peningkatan Pengetahuan Masyarakat mengenai Diabetes Melitus di Desa Koto Majidin Mudik Kabupaten Kerinci - Hendra, Gabriel Septian; Rahmaddiansyah, Refa (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
Diabetes mellitus is one of the chronic diseases that has received attention in Indonesia. The International Diabetes Federation (IDF) stated that diabetes is among the global emergencies with the fastest growth in the 21st century. The prevalence of this disease is estimated to continue increasing worldwide. Health promotion is one of the preventive efforts that can be undertaken, one of which is through educational methods. The aim is for the community to have sufficient knowledge so that they are willing to maintain and preserve their health. Increasing knowledge about diabetes is crucial to raise awareness of health maintenance. Health education can be implemented in community service activities. This activity was carried out on July 30, 2023, in Koto Majidin Mudik Village, Kerinci Regency, Jambi Province. The activity was conducted through the stages of preparation, implementation, and evaluation. The activity was carried out by the Community Service (KKN) team from Andalas University 2023, Koto Majidin Mudik Village, which was a collaboration of various departments, working in cooperation with the village and the Kemantan Community Health Center (Puskesmas). During the implementation of the activity, the community actively participated. Through the evaluation conducted at the end of the activity, the village, health center, and the community provided positive responses. The results of this community service are expected to provide knowledge, especially in the prevention of diabetes mellitus, and an understanding of healthy lifestyles, thereby forming a healthy community for the future quality of human resources.